"Waiting for the Other Shoe to Drop": Waiting for Health Care and Duration of Sick Leave - Daniela Andrén; David Granlund (Örebro University School of Business, 2010)
This paper uses a labor supply model that incorporates waiting for health care to derive an empirical specification for sick leave and to estimate the impact of waiting for health care on the duration of sick leave. In the estimations, we use the 2002 sample of the RFV-LS register database, supplemented with information from questionnaires. The results indicate that almost all waiting for health care variables have a statistically significant positive impact on the duration of sick leave, and did not induce substantial changes on the impact of traditional variables of the labor supply model.
Keywords: I12; J21; J28; 330; sick leave; waiting list